Corpus-based foreign-language textbooks: using the cognitive resources of older learners efficiently - Ramírez-Gómez, Danya; Sanz, Montserrat (Linguarum Arena, 2017)
The presence of older learners (60 years old and over) in the foreign language (FL) classroom is increasingly common. However, although these students differ from younger ones in a variety of cognitive, physical and psychological aspects, textbooks have not yet been adapted to the characteristics of the former. This lack of teaching materials entails either that older learners be unable to study an FL with a textbook that addresses their needs and interests, or that teachers must constantly collect materials from different sources, which is exceedingly time consuming. The objective of this article is to start a debate on potential modifications to Spanish teaching materials that respond to older learners’ needs, specifically for initial level learners. This study discusses modifications that address two significant issues: the introduction of vocabulary, and the introduction of grammar tenses and conjugations. These two issues generate important challenges in the learning process of the cohort under discussion (Ramírez Gómez 2016). The framework for this work is the analysis of the Corpus del Español (Davies 2002), which includes more than 100 million entries. The study explores the most frequently used content words of Spanish (e.g. nouns, verbs, adjectives) and contrasts these data with how current and popular Spanish textbooks introduce this information. The analysis indicates that textbooks present vocabulary and grammar tenses and conjugations in a manner that fails to reflect actual Spanish use, despite this being one of the main objectives of the functional-approach, which is followed by most of the textbooks revised here. Also, drawing from previous studies on age-related cognitive transformations, transitivity, aspect, among others, we argue that textbooks for initial level learners – particularly for older learners – should centre on the acquisition of highly frequent and relatable vocabulary to elevate their exposure to relevant structures and foster memorization. Additionally, textbooks should also present verb tenses and conjugations in a balanced fashion that pays more attention to prototypical structures of Spanish. The conclusions of this article are relevant because they question the status quo regarding how to introduce structures and vocabulary to initial level learners. Also, they suggest textbook modifications that may help older adults make more efficient use of their cognitive resources, enhance memorization and thus overcome some of their most important challenges when learning an FL.